DETERMINANTS OF INPATIENT SATISFACTION IN FOOD SERVING AND FOOD SERVICE AT MELATI HOSPITAL TANGERANG - Nafi'a, Zidni Ilma; Suryani, Dyah; Solikhah, Solikhah (JURNAL KESMAS DAN GIZI (JKG), 2023)
Hospital is one of the health service industries that has an important role in providing health services to the community. One of the services at the hospital is hospital nutrition service activities which consist of outpatient nutrition care, inpatient nutrition care, food administration, and research and development. Many parties often pay attention to the organization of food in hospitals, in this case, inpatient food services because it is related to patient satisfaction. This study aims to determine the determinants associated with inpatient satisfaction in serving and serving food. The research method used is the chi-square correlation. The sample in this study were inpatients at Melati Hospital Tangerang, totaling 193 patients. The sampling technique used purposive sampling and was taken using a questionnaire. The significance values of the variables age, gender and education were 0.035, 0.048 and 0.018 less than ? (0.05) while the significance values of the variables of work and type of diet were 0.637 and 0.642 more than ? (0.05). This study obtained the results that there was a significant relationship between age, gender and education with service satisfaction and food serving, while work and type of diet did not have a significant relationship with food serving and service. Keywords: Food Service, Food Serving, Patient Satisfaction, Chi-square